Variations in different preceding crops on the soil environment, bacterial community richness and diversity of tobacco-planting soil - Liu, Ming; Xue, Rujun; Wang, Dexun; Hu, Yanxia; Gu, Kaiyuan; Yang, Liu; Zhao, Jie; Guan, Shuyue; Su, Jiaen; Jiang, Yonglei (Frontiers in Microbiology, 2024)
Tobacco (Nicotiana tabacum L.) is a major cash crop, and soil quality played a significant role in the yield and quality of tobacco. Most farmers cultivate tobacco in rotation with other crops to improve the soil characteristics. However, the effects of different previous crops on the soil’s nutrient status and bacterial community for tobacco cultivation still need to be determined. Three treatments were assessed in this study, i.e., tobacco-planting soil without treatment (CK), soil with barley previously cultivated (T1), and soil with rapeseed previously cultivated (T2). The soil physical and chemical properties and the 16S rRNA gene sequence diversity of the bacterial community were analyzed. The effects of different crops on the physical and chemical properties of tobacco-planting soil and the diversity and richness of the bacterial community were comprehensively discussed. The results of this study showed that different previously cultivated crops altered the nutrient status of the soil, with changes in the ratio of NH4+-N to NO3−-N having the most significant impact on tobacco. In CK, the ratio of NH4+-N to NO3−-N was 1:24.2, T1–1:9.59, and T2–1:11.10. The composition of the bacterial community in tobacco-planting soil varied significantly depending on the previously cultivated crops. The richness and diversity of the bacterial community with different crops were considerably higher than without prior cultivation of different crops. The dominant bacteria in different treatments were Actinobacteriota, Proteobacteria, and Chloroflexi with their relative abundance differed. In conclusion, our study revealed significant differences in nutrient status, bacterial community diversity, and the richness of tobacco-planting soil after the preceding cultivation of different crops. Suitable crops should be selected to be previously cultivated in tobacco crop rotations in near future for sustainable agriculture.